1994
DOI: 10.1159/000119077
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and Hormones Related to the Hypothalamic-Pituitary-Adrenal Axis Modulate Inherited Neocortical Spindling in DBA/2J Mice

Abstract: The role of dexamethasone and hormones related to the hypothalamic-pituitary-adrenal (HPA) axis (corticotropin-releasing factor, adrenocorticotropic hormone, corticosterone) in the control of the spike-and-wave spindling episodes (S&W) which can be spontaneously recorded in the electrocorticogram (ECoG) of DBA/2J mice was investigated. Both dexamethasone and hormones related to the HPA axis consistently reduced the S&W in DBA/2J mice. Cyclo-heximide (a protein synthesis inhibitor) pretreatment significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
4
5
0
Order By: Relevance
“…Furthermore, these data indicate that the time necessary for the appearance of this effect is very similar to that observed previously on brain excitability after DEX administration in vivo [4,5] and in vitro [4,33]. These data and those obtained with actinomycin D are consistent with the genomic activation induced by DEX via an intracellular receptor mechanism, in agreement with the steroid hormone mechanism of action model proposed by Thompson and Lippman [66].…”
Section: Dopaminergic Pathwaysupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, these data indicate that the time necessary for the appearance of this effect is very similar to that observed previously on brain excitability after DEX administration in vivo [4,5] and in vitro [4,33]. These data and those obtained with actinomycin D are consistent with the genomic activation induced by DEX via an intracellular receptor mechanism, in agreement with the steroid hormone mechanism of action model proposed by Thompson and Lippman [66].…”
Section: Dopaminergic Pathwaysupporting
confidence: 90%
“…Also, it is well known that glucocorticoids effects may become evident a few minutes [28,29] or 1-2 hr after administration: in this case, glucocorticoids exert their effect through a genomic activation [30][31][32]. Also, some previous studies are in according with the latter findings because DEX needs a certain lag-rime (15-30 min) to reduce brain excitability and cycloheximide was able to block the DEX effects [4,5,33]. Therefore, to verify a possible involvement of a genomic activation in the reducing effect of DEX on morphine, amphetamine and cocaine hypermotility, the steroid was administered at different time intervals before morphine, amphetamine or cocaine injection, and the influence of actinomycin D (dacrinomycin), a protein synthesis inhibitor [34], on the steroid effects was considered.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the WAG/ Rij rats, an absence epilepsy model, show a rapid, albeit transient increase in the number of absence seizures in response to the administration of CORT (Schridde and van Luijtelaar, 2004). In contrast, administration of CORT to absence seizure-prone DBA/2J mice decreased the number of spontaneous spike and wave discharges observed (Capasso et al, 1994).…”
Section: Effects Of Corticosterone On Seizuresmentioning
confidence: 96%
“…Experimental data showed that cortisone and hydrocortisone facilitate kindling development [16,17], lower the seizure threshold [18,19] Di Giannuario/Pieretti/Sagratella/Loizzo spikes in the hippocampus, hypothalamus, amygdala and septum [20]. On the other hand, it has been reported that dexamethasone reduces spontaneous spike and spindling episodes (S&W) in DBA/2J mice [21] and blocks the epileptiform activity induced by morphine in the rabbit hippocampus in vivo [10] and by the Ì-opioid agonist [DAla 2 -N,Me-Phe 4 -Gly 5 -ol]enkephalin (DAMGO), or by picrotoxin in rat hippocampal slices [10] and in organotypic cell culture in vitro [22]. Clinical data also confirm that glucocorticoids may have anti-epileptic properties as observed in the early treatment of some infantile spasms with ACTH or corticosteroids which produce a remission of seizure activity and epileptiform EEG patterns [23][24][25].…”
Section: Introductionmentioning
confidence: 99%